(untitled) (Global Journal of Human-Social Science, 2020)
This study examines the effect of inventory management on organizational operations, productivity, as a means of causing the profitability of companies. The study was, therefore designed to study how the manufacturing firms managed their inventory materials. We used questionnaire in collecting our data. The data collected was analysed using spearman’s rank-order correlation coefficient and the Pearson product-moment correlation coefficient. The findings indicated that the method used by 7Up Bottling Company to manage their inventories in both raw materials and the finished product was efficient as the amount of naira saved in the course of purchase have more effect on the profitability of the company during production/ selling of the finished goods. Controlled purchasing is found to be costeffective. The study recommends the following: an adoption and application of the economic order quantity (EOQ) model to save cost and make the operations more efficient.